N6-methyladenosine Regulator-Mediated Immune Genes Identify Breast Cancer Immune Subtypes and Predict Immunotherapy Efficacy - Zhang, Meng-Meng; Lin, Yi-Lin; Zeng, Wen-Feng; Li, Yang; Yang, Yang; Liu, Miao; Ye, Ying-Jiang; Jiang, Ke-Wei; Wang, Shu; Wang, Shan (Frontiers in Genetics, 2021)
Breast cancer (BRCA) is a heterogeneous malignancy closely related to the tumor microenvironment (TME) cell infiltration. N6-methyladenosine (m6A) modification of mRNA plays a crucial regulator in regulating the immune microenvironment of BRCA. Immunotherapy represents a paradigm shift in BRCA treatment; however, lack of an appropriate approach for treatment evaluation is a significant issue in this field. In this study, we attempted to establish a prognostic signature of BRCA based on m6A-related immune genes and to investigate the potential association between prognosis and immunotherapy. We comprehensively evaluated the m6A modification patterns of BRCA tissues and non-tumor tissues from The Cancer Genome Atlas, as well as the modification patterns with TME cell-infiltrating characteristics. Overall, 1977 TME-related genes were identified in the literature. Based on Lasso and Cox regression analyses, the m6A-related immune score (m6A-IS) was established to characterize the TME of BRCA, predict prognosis and efficacy associated with immunotherapy. We developed an m6A-IS to effectively predict immune infiltration and prognosis of patients with BRCA. The prognostic score model represented robust predictive performance in both the training and validation cohorts. The low m6A-IS group was characterized by enhanced antigen presentation and improved immune checkpoint expression, further indicating sensitivity to immunotherapy. Compared with the patients in the high-score group, overall survival rate after treatment in the low-score group was significantly higher in the testing and validation cohorts. We constructed an m6A-IS system to examine the ability of the m6A signature to predict the infiltration of immune cells of the TME in BRCA, and the m6A-IS system acted as an independent prognostic biomarker that predicts the response of patients with BRCA in immunotherapy.